2012
DOI: 10.1007/8904_2012_157
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Consequences of Adhering to a Low Phenylalanine Diet for Late-Treated Adults with PKU

Abstract: Background: The main treatment for phenylketonuria (PKU) is a low phenylalanine (Phe) diet, phenylalaninefree protein substitute and low-protein special foods. This study describes dietary composition and nutritional status in late-diagnosed adult patients adhering to a PKU diet.Methods: Nineteen patients, followed at Oslo University Hospital in Norway, participated; median age was 48 years (range 26-66). Subjects were mild to severely mentally retarded. Food intake, clinical data and blood analyses relevant f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
(18 reference statements)
2
8
0
Order By: Relevance
“…Our findings are in accordance with other studies reporting about twice as high folate levels in PKU children and young adults than in controls (Colome et al 2003;Huemer et al 2008). A recent report of 19 Norwegian latetreated adults found high intakes of folic acid and corresponding high blood folate concentrations (Wiig et al 2013). Only one PKU center in Greece reported of lower folate levels in PKU children with good compliance compared to PKU children with less adherence to diet and to controls (Schulpis et al 2002).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings are in accordance with other studies reporting about twice as high folate levels in PKU children and young adults than in controls (Colome et al 2003;Huemer et al 2008). A recent report of 19 Norwegian latetreated adults found high intakes of folic acid and corresponding high blood folate concentrations (Wiig et al 2013). Only one PKU center in Greece reported of lower folate levels in PKU children with good compliance compared to PKU children with less adherence to diet and to controls (Schulpis et al 2002).…”
Section: Discussionsupporting
confidence: 92%
“…Another study of 19 Norwegian late-treated adults found that about 85 % of dietary folate equivalents (DFEs) originated from folic acid in the protein substitute. The remaining 15 % were from specially manufactured low protein foods, vegetables, fruits, and small amounts of dairy products (Wiig et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Five patients reported an intake above SAR (Table 2). Because all patients off diet showed serum concentrations within normal range, elevated serum concentrations appear to be due to fortified AAM [37]. Our findings are confirmed by the study by Stolen et al [38] reporting similar results.…”
Section: Discussionsupporting
confidence: 83%
“…In phenylketonuria patients (PKU; OMIM261600), the conversion of phenylalanine (Phe) to tyrosine is blocked, due to disruption of the activity phenylalanine hydroxylase enzyme (PAH; EC 1.14.16.1) in the liver (Wiig et al 2012). Notwithstanding, Phe is an essential amino acid and is important to ensure normal anabolism.…”
Section: Introductionmentioning
confidence: 99%